The Consequences of Miscarriage on Parental Investments - Aline Bütikofer; Deirdre Coy; Orla Doyle; Rita Ginja (Center for Economic Studies and ifo Institute (CESifo), 2024)
Pregnancy loss is often a traumatic event which may impact both parents and subsequent children. Using Norwegian registry data, we exploit the random nature of single, early miscarriages to examine the impact of pregnancy loss on parental investment and family outcomes. We find that pregnancy loss improves maternal health investments in the subsequent pregnancy regarding supplement use, smoking, preventative healthcare, and physician choice. While a miscarriage negatively affects labor market attachment, it has limited effects on children born after the loss. This suggests that investment in the next pregnancy may offset the negative consequences of stress associated with pregnancy loss.
Keywords: I12; J13; 330; miscarriage; parental investment; healthcare use; household labor supply